Intelligent Computing Proceedings of the 2019 Computing Conference, Volume 2 - Arai, Kohei; Bhatia, Rahul; Kapoor, Supriya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the Computing Conference 2019, providing a comprehensive collection of chapters focusing on core areas of computing and their real-world applications. Computing is an extremely broad discipline, encompassing a range of specialized fields, each focusing on particular areas of technology and types of application, and the conference offered pioneering researchers, scientists, industrial engineers, and students from around the globe a platform to share new ideas and development experiences. Providing state-of-the-art intelligent methods and techniques for solving real- world problems, the book inspires further research and technological advances in this important area.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence